Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.13104/imri.2017.21.3.139
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI of Prostate Cancer after Biopsy: Little Impact of Hemorrhage on Tumor Staging

Abstract: Original ArticlePurpose: To evaluate differences in staging accuracy of prostate cancer according to the extent of hemorrhage on multiparametric MRI performed after biopsy. Materials and Methods:We enrolled 71 consecutive patients with biopsy-proven prostate cancer. Patients underwent MRI followed by a prostatectomy at our institution in 2014. Two radiologists reviewed the MRI to determine the tumor stage. Correlation between biopsy-MRI interval and extent of hemorrhage was evaluated. Regression analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…MRI scan of each patient was performed using 3T scanners (TIM Trio, Siemens, Erlangen, Germany) 6–8 weeks after the prostate biopsy procedure ( 26 ). The MRI protocol was derived from the European Society of Uro-radiology (ESUR) guidelines 2012 ( 27 ) for PCa detection; PIRADS v2.0 was applied in this study, and only PIRAD ≥3 lesions on MRI were marked and PIRADS 1 and 2 were taken as negative findings.…”
Section: Methodsmentioning
confidence: 99%
“…MRI scan of each patient was performed using 3T scanners (TIM Trio, Siemens, Erlangen, Germany) 6–8 weeks after the prostate biopsy procedure ( 26 ). The MRI protocol was derived from the European Society of Uro-radiology (ESUR) guidelines 2012 ( 27 ) for PCa detection; PIRADS v2.0 was applied in this study, and only PIRAD ≥3 lesions on MRI were marked and PIRADS 1 and 2 were taken as negative findings.…”
Section: Methodsmentioning
confidence: 99%
“…2 ). Choi et al [ 19 ] showed that staging in magnetic resonance imaging was not associated with the post-biopsy interval. It is also thought that the amount of bleeding is not related to the interval.…”
Section: Optimal Timementioning
confidence: 99%
“…It is also thought that the amount of bleeding is not related to the interval. [ 17 , 19 ] There is no consensus on this matter.…”
Section: Optimal Timementioning
confidence: 99%
“…In general, prostate MRI should not be performed within 8-12 weeks following prostate biopsy to allow sufficient time for resolution of blood products related to prostate biopsy, although large variations in presence and resolution of post-biopsy blood products in individual patients have been reported. [19][20][21] In the presence of blood products, prostate cancer can appear as hypointense area what some authors call as 'haemorrhage exclusion sign' which is defined as presence of a well-defined area of low signal intensity surrounded by areas of high signal intensity on T1-weighted images.…”
Section: Basics Of Mri Physics With Emphasis On Prostate Mrimentioning
confidence: 99%